HIV and other STIs self-testing to reduce risk compensation among men who have sex with men who use oral pre-exposure prophylaxis in China: protocol for a randomised waitlist-controlled trial. Issue 7 (19th July 2020) - Zhang, Jing; Huang, Xiaojie; Chen, Yaokai; Wang, Hui; Zhang, Yonghui; Wang, Hongyi; Mei, Zhu; Jia, Yueru; Chu, ZhenXing; Hu, Qing-Hai; He, Xiaoqing; Zhang, Lukun; et al.
Abstract : Introduction: Pre-exposure prophylaxis (PrEP) reduces the risk of HIV infection among men who have sex with men by up to 99%. However, in real-world settings, PrEP users may exhibit risk compensation after uptake of PrEP, including more condomless anal intercourse (CAI) and increased sexually transmitted infection (STI) acquisition. HIV self-testing (HIVST) decreases CAI among men who have sex with men (MSM) by providing awareness of the HIV status of oneself and one's sexual partners. Here, we describe the rationale and design of a randomised waitlist-controlled trial to examine the impact of HIVST on risk compensation among PrEP users. Methods and analysis: The study is a two-arm randomised waitlist-controlled trial with 1000 HIV-negative MSM in four major cities in China who will be taking oral PrEP (involving tenofovir disoproxil fumarate/emtricitabine) either daily (n=500) or in an event-driven regimen (n=500). The participants will be randomised (1:1) to either the immediate HIVST intervention arm (HIVST plus standard facility-based counselling and testing from 0 to 12 months) or the waitlist arm (standard facility-based counselling and testing from 0 to 6 months, then crossover to receive the HIVST intervention in months 7–12). Participants will provide blood samples to assess the incidence of syphilis and herpes simplex virus type 2 (HSV-2) during a follow-up. The primary outcomes will be the occurrence of CAI, number of sexual partners and incidence of syphilis and HSV-2 during a follow-up. The secondary outcomes will be the HIV and STI testing frequency and STI treatment adherence during a follow-up. The planned start and end dates for the study is 26 December 2018 and 31 December 2020. Ethics and dissemination: The Medical Science Research Ethics Committee of The First Affiliated Hospital of China Medical University has approved the study (IRB(2018)273). Trial registration number: ChiCTR1800020374